Design of AC Microgrid Topology with Photovoltaic Uncertainties in a Rural Village - Vai, Vannak (Makara Journal of Technology, 2021)
Energy needs are increasing day by day, especially for developing countries, due to population growth and changing lifestyles. A suitable microgrid topology with renewable energy integration is considered to fulfill the people and society’s needs. This paper focuses on the design of AC microgrid topology for a nonelectrified village with the integration of PV uncertainties in both sitting and sizing. The development of an optimal algorithm based on the conductor use minimization and unbalanced load improvement is proposed. The shortest path is proposed to search for the minimum conductor use. Then, the algorithm for improving the unbalanced load with two different algorithms–phase sequence and first-fit bin packing with phase swapping–is compared based on the energy use indicator. Once the optimal AC microgrid topology is defined, the impact of the integration of PV uncertainties into the system is studied. Simulation results prove the effectiveness of the proposed method.